2007
DOI: 10.1159/000103905
|View full text |Cite
|
Sign up to set email alerts
|

Availability Influences Initial and Continued Ingestion of Nicotine by Adolescent Female Rats

Abstract: Background: The availability of tobacco products is associated with the likelihood that adolescents will begin using tobacco. Yet the relationship between nicotine availability and voluntary consumption has not been tested experimentally in developing rats. Method: The impact of environmental availability on adolescent female rats’ initial reaction to and continued ingestion of a novel solution (nicotine or control) was compared using a standard 2-bottle free-choice method and a multiple-bottle method. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 93 publications
0
14
0
Order By: Relevance
“…During the first 7 days of the experiment, all mice were exposed to three glass drinking bottles filled with water or nicotine for 22 hours a day, and a single water bottle for two hours each day. For mice in the control group (N=12), all 3 bottles were filled with tap water, and for mice in the nicotine group (N=14) all 3 bottles were filled with 200 μg/ml (-)-nicotine freebase dissolved in tap water [the multiple bottle protocol was used to produce pronounced nicotine intake (Biondolillo & Pearce, 2007; Halder et al, 2013)]. This nicotine concentration was selected as adolescent mice voluntarily consume nicotine at this concentration without any signs of adverse side effects (Klein et al, 2003; 2004).…”
Section: Methodsmentioning
confidence: 99%
“…During the first 7 days of the experiment, all mice were exposed to three glass drinking bottles filled with water or nicotine for 22 hours a day, and a single water bottle for two hours each day. For mice in the control group (N=12), all 3 bottles were filled with tap water, and for mice in the nicotine group (N=14) all 3 bottles were filled with 200 μg/ml (-)-nicotine freebase dissolved in tap water [the multiple bottle protocol was used to produce pronounced nicotine intake (Biondolillo & Pearce, 2007; Halder et al, 2013)]. This nicotine concentration was selected as adolescent mice voluntarily consume nicotine at this concentration without any signs of adverse side effects (Klein et al, 2003; 2004).…”
Section: Methodsmentioning
confidence: 99%
“…When rodents are given a choice of water or a nicotine solution, consumption shows individual variability, including sex and age differences (Abreu-Villaca et al, 2006; Adriani et al, 2002a, b; Biondolillo and Pearce, 2007; Dadmarz and Vogel, 2003; Flynn et al, 1989; Glatt et al, 2009; Isiegas et al, 2009; Kameda et al, 2000; Klein et al, 2004; Lee et al, 2004; Li et al, 2007; Maehler et al, 2000; Marshall et al, 2003; Pawlak and Schwarting, 2002; Robinson et al, 1996; Todte et al, 2001; Vieyra-Reyes et al, 2008). When nicotine is administered orally, the blood levels do not rise as quickly as intravenous application, subsequently the effects are relatively more subtle.…”
Section: Introductionmentioning
confidence: 99%
“…These genetic effects are seen when inbred mouse strains are tested using a 2-bottle choice procedure (Li et al, 2007; Portugal and Gould, 2008; Robinson et al, 1996) and when F2 hybrids derived from inbred strains are tested (Butt et al, 2005; Li et al, 2007). Many studies (see, for examples: (Biondolillo and Pearce, 2007; Flynn et al, 1989; Pawlak and Schwarting, 2002; Vieyra-Reyes et al, 2008)) have used the rat to study oral nicotine self-administration, but most of these studies used a single strain. Nonetheless, comparisons of the results obtained in these studies suggest that inbred and outbred rat strains differ in oral nicotine intake.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies counterbalance the position of the bottles containing drug and vehicle solutions across subjects, but keep bottles in the same position for the same animal (e.g. [29, 40]). Recent studies have demonstrated that side preference is largely eliminated if food pellets are placed around both bottles [50] or if the drug and vehicle bottles are placed on the same cage wall an equal distance away from the food hopper [40].…”
Section: Animal Models Of Oral Drug Intakementioning
confidence: 99%
“…Nonetheless, the finding that WKR rats consumed more nicotine than the BNR suggests that genetic factors influence oral nicotine intake. Less convincing support for the assertion that genetic factors influence oral nicotine intake comes from studies that used only one rat strain [29, 31, 41, 45]. However, when these studies are compared it is readily evident that the strains differ in oral nicotine intake.…”
Section: Do Genetic Factors Influence Oral Alcohol or Nicotine Intake?mentioning
confidence: 99%